Operationalizing longitudinal approaches to climate change vulnerability assessment in the Arctic - Fawcett, David; Pearce, T; Ford, J; Archer, L (ArcticNet Inc., 2016)
The last decade has seen a proliferation of community-scale climate change vulnerability assessments globally, and specifically in the Arctic. Many of these have employed a vulnerability framework, drawing upon interviews with community members to identify and characterize climatic risks and adaptive responses. This has led to the development of useful baseline understandings of vulnerability and adaptation. However, these understandings aretemporally static; because vulnerability and adaptation are dynamic processes, new methodologies are needed to generate insights on the dynamics of how climate change is experienced and responded to by communities and individuals. The use of longitudinal approaches to capture the dynamism of human processes is wellestablished in sociology and the health sciences, but the uptake of such approaches remains limited in climate change vulnerability research. Therefore, we propose the application of two longitudinal approaches – cohort and trend studies – in climate change vulnerability assessment and review three case studies from ArcticNet research in the Canadian Arctic. These case studies offer an example of how longitudinal approaches can be operationalized in vulnerability research in the Arctic, and globally, to capture the dynamism of vulnerability through the identification of climatic anomalies and trends, the temporal development of adaptive pathways and the effects of interactions and convergences between conditions, and insights on themes critical to understanding adaptation such as social learning and knowledge sharing. This research is part of ArcticNet Project 1.1 Community Vulnerability, Adaptation and Resilience to Climate Change in the Arctic.